2018
DOI: 10.1080/13504851.2018.1486984
|View full text |Cite
|
Sign up to set email alerts
|

The role of transaction costs and risk aversion when selecting between one and two regimes for portfolio models

Abstract: We wish to thank Chris Brooks and Ioannis Oikonomou (Reading), and Xiaoxia Ye (Bradford) for their comments on an earlier draft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To control for this, in our final robustness check we allow for the presence of two market regimes which have different asset means, variances and correlations. We applied the regimes methodology used by Platanakis et al (2019b) and used a Taylor series expansion for the CRRA utility function to incorporate higher moments in the portfolio construction process. We ruled out short sales and estimated a two-state multivariate regime switching model for each 60 month rolling window for λ = 2, 5 and 10.…”
Section: [Insert Table 12 About Here]mentioning
confidence: 99%
“…To control for this, in our final robustness check we allow for the presence of two market regimes which have different asset means, variances and correlations. We applied the regimes methodology used by Platanakis et al (2019b) and used a Taylor series expansion for the CRRA utility function to incorporate higher moments in the portfolio construction process. We ruled out short sales and estimated a two-state multivariate regime switching model for each 60 month rolling window for λ = 2, 5 and 10.…”
Section: [Insert Table 12 About Here]mentioning
confidence: 99%
“…Ouattara et al (2019) focused on a representative farmer’s attitude toward risk; the results reveal that crop production is highly affected by the farmer’s attitude toward risk. Platanakis et al (2019) investigated US data and concluded that differences in risk preference cause investors to prefer different investment models. The above literature review shows that risk aversion has a profound impact on decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the seminal work of Hamilton (1989), HM models have been fruitfully applied in diverse areas such as communications engineering and bioinformatics Cappé et al (2006). In finance, they have been extensively used in predicting and explaining exchange rates Panopoulou and Pantelidis (2015); Lee and Chen (2006); Frömmel et al (2005); Bollen et al (2000), stock market returns Dias et al (2015); Angelidis and Tessaromatis (2009); Guidolin and Timmermann (2006), business cycles Tian and Shen (2019); Chauvet and Hamilton (2006), realized volatility Koki et al (2020); Liu and Maheu (2018), the behavior of commodities Pereira et al (2017) and in portfolio allocation Platanakis et al (2019). The reason for their increased popularity is that they present various attractive features.…”
Section: Other Related Literaturementioning
confidence: 99%